Synthesis and Crystal Structure of Fumaropimaric Acid Triacid Amide - Song, Xing; Zhou, Yonghong; Zhang, Meng; Yang, Xiaohui (Asian Journal of Chemistry, 2010)
The compound fumaropimaric acid triacid amide was synthesized by acyl chlorination and ammonolysis reaction between fumaropimaric acid and SOCl2 and aqueous ammonia. It was characterized by single crystal X-ray diffraction. The colourless crystals crystallized in the orthorhombic system, space group P212121 with cell dimensions: a = 7.2910(15) Å, b = 15.221(3) Å, c = 21.822(4) Å, a = 90º, b = 90º, g = 90º, V = 2421.7(8) Å3 and R1 = 0.0645, wR2 = 0.1404. The two fused and unbridged cyclohexane rings have chair conformations. The other rings are twistboat forms. The molecular structure includes two molecules (fumaropimaric acid triacid amide and methanol). The molecules are linked by hydrogen bonds and van der Waals forces. The crystal structure has been deposited at the Cambridge crystallographic data centre and allocated the deposition number CCDC 790373.